2022
DOI: 10.3389/fmars.2022.985195
|View full text |Cite
|
Sign up to set email alerts
|

Ecological risk assessment of metallic nanoparticles on the marine environments: Species sensitivity distributions analysis

Abstract: Metallic nanoparticles (NPs) are increasingly being used and inevitably entering the marine environment. Therefore, the adverse effects of NPs on individual marine species have attracted increasing attentions. However, to date, the ecological risks of NPs on the marine ecosystem remain poorly understood. In this study, species sensitivity distributions (SSDs) were constructed for Ag, ZnO, CuO, and TiO2 NPs to understand their ecotoxicity to the marine ecosystem and the contribution of size effect and ion effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Moreover, the aluminum concentrations in soils can vary from scarce from 0.0003 to 0.047 g kg (France) to very high from 33.0 to 128.5 g/kg (Japan, China). Barretto et al and Feng et al reported that there is limited data regarding the concentrations of metal nanoparticles in the aquatic environment 45 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the aluminum concentrations in soils can vary from scarce from 0.0003 to 0.047 g kg (France) to very high from 33.0 to 128.5 g/kg (Japan, China). Barretto et al and Feng et al reported that there is limited data regarding the concentrations of metal nanoparticles in the aquatic environment 45 47 .…”
Section: Discussionmentioning
confidence: 99%